Catalytic Au(i)/Au(iii) arylation with the hemilabile MeDalphos ligand: unusual selectivity for electron-rich iodoarenes and efficient application to indoles. Issue 30 (25th June 2019) - Rodriguez, Jessica; Zeineddine, Abdallah; Sosa Carrizo, E. Daiann; Miqueu, Karinne; Saffon-Merceron, Nathalie; Amgoune, Abderrahmane; Bourissou, Didier
Abstract : The ability of the MeDalphos ligand to trigger oxidative addition of iodoarenes preferentially electron-rich, to gold has been thoroughly studied and exploited to develop an efficient Au(i )/Au(iii )-catalysed C3-arylation of indoles. Abstract : The ability of the hemilabile (P, N) MeDalphos ligand to trigger oxidative addition of iodoarenes to gold has been thoroughly studied. Competition experiments and Hammett correlations substantiate a clear preference of gold for electron-enriched substrates both in stoichiometric oxidative addition reactions and in catalytic C–C cross-coupling with 1, 3, 5-trimethoxybenzene. This feature markedly contrasts with the higher reactivity of electron-deprived substrates typically encountered with palladium. Based on DFT calculations and detailed analysis of the key transition states (using NBO, CDA and ETS-NOCV methods in particular), the different behavior of the two metals is proposed to result from inverse electron flow between the substrate and metal. Indeed, oxidative addition of iodobenzene is associated with a charge transfer from the substrate to the metal at the transition state for gold, but opposite for palladium. The higher electrophilicity of the gold center favors electron-rich substrates while important back-donation from palladium favors electron-poor substrates. Facile oxidative addition of iodoarenes combined with the propensity of gold(iii ) complexes to readily react with electron-rich (hetero)arenes prompted us to apply the (MeDalphos)AuCl complex in the catalytic arylation of indoles, a challenging but very important transformation. The gold complex proved to be very efficient, general and robust. It displays complete regioselectivity for C3 arylation, it tolerates a variety of functional groups at both the iodoarene and indole partners (NO2, CO2 Me, Br, OTf, Bpin, OMe…) and it proceeds under mild conditions (75 °C, 2 h).